Myeloid sarcoma of the middle ear mimicking otitis media – diagnostic and therapeutic challenges - Jacek Sokołowski; Michał Jerzy Górka; Beata Gierej; Emilia Wnuk; Robert Bartoszewicz; Agnieszka Tomaszewska; Kazimierz Niemczyk (Acta Haematologica Polonica)
Myeloid sarcoma (MS) is a rare manifestation of acute myeloid leukemia (AML), mostly developing within the skin, the bones or the lymph nodes. Here we report an ultrarare case of the middle ear MS, initially misdiagnosed as otitis media. The initial presentation was facial nerve paresis, acute otitis media symptoms, and hearing loss. Eventually a diagnosis of MS with translocation t(8;21)(q22;q22) was made with CNS and bone marrow involvement. The treatment comprised high-dosed cytarabine and allogeneic hematopoietic cell transplantation. In the manuscript we discuss the diagnostic challenges of MS of the temporal bone, as well as the potential treatment options.